Legal Ramifications of Unregistered Divorce in the Religious Court within the Mandailing Natal Community - Hamid, Asrul; Ritonga, Raja; Siregar, Resi Atna Sari; Akhyar, Akhyar; Nasution, Suryadi (El-Usrah: Jurnal Hukum Keluarga, 2024)
The legal dualism in the Mandailing Natal community between the rules of school fiqh and the laws and regulations regarding divorce issues still leaves problems. This research aims to answer the phenomenon of divorce outside the Religious Courts in the Mandailing Natal community and the factors that influence it, then the legal consequences that occur in the Mandailing Natal community. This study uses sociological legal methods with a legislative approach and is analyzed philosophically. Data was collected by means of literature study and observation. The study found that the rules in fiqh state that divorce can be carried out anywhere and at any time without being limited by space and time as long as harmony and conditions are met, while the rules in legislation such as the Marriage Law, the Religious Courts Law and the Compilation of Islamic Law ( KHI) states that divorce can only be carried out in front of a court hearing, in other words, there are rules that must be fulfilled when seeking a divorce. The legal consequences of divorce outside the Religious Courts show that the legal rules were made with the aim of maintaining benefits and avoiding mafsadat. So the public needs to understand that even though divorce is a private matter, the presence of the government is an effort to guarantee the rights and legal protection of the community. So that Islamic law can be seen from various aspects of life, so that the goal of sharia, namely legal certainty and order, can be realized.